Non-covalent Interactions Directed Rearrangement of Lactones to Pyrones: A Computational Study on the Mechanistic Insights of Solvent Assisted Gold(I) Catalyzed Reactions - Gayatri, G. (Journal of Scientific Research, 2021)
The mechanism of gold(I) catalyzed cycloisomerization of lactones to pyrones was analyzed by performing DFT study using B3LYP method with LanL2DZ basis set for Au and 6-31g(d) basis set for all other atoms. The potential energy surface of the reaction was scanned to know the preferred path for the formation of products under gas phase. The effects of solvent using acetonitrile, dichloromethane and toluene are explored as these solvents are reported to play a crucial role in the final product formation. The crossover between the oxophilic and alkynophilic reaction complexes, R-O and R-C, is found to be the major driving force which directs the product formation. While the larger energy gap between R-O and R-C leads to pyrone formation, the smaller difference and in turn the rapid crossover between R-O and R-C leads to the formation of decarboxylation adduct. Counterion plays a major role throughout the reaction. The atoms in molecules analysis on R-C using implicit as well as explicit solvent gave reason for the observed experimental trends and suggest that the prevailed non-covalent interactions play a substantial role in the product formation.